The impact of Wordwall on Pronunciation, Stress placement and Intonation Improvement in English for Psychology students: A case of Georgian university - Mari Makharashvili (European Scientific Journal, ESJ, 2025)
This study examines the effectiveness of the Wordwall online game application in improving pronunciation, stress placement, and intonation for B2-level English for Psychology students. 60 Georgian university students participated, with 30 in the experimental group (using Wordwall) and 30 in the control group (using traditional methods). Students recorded 10 challenging words using smartphones and computers and submitted them to the researcher before and after a semester of learning. The recordings were evaluated using a rubric, and data were analyzed with SPSS 24.00. Statistical analysis, using the Wilcoxon Signed-Rank and Mann-Whitney U Tests, showed significant improvements in pronunciation and intonation in the experimental group (p-value < 0.05). Positive feedback from students highlighted Wordwall’s effectiveness. The findings suggest that game-based learning is a valuable tool for improving language skills.